Inclusive Education for Refugee Children With Disabilities in Berlin—The Decisive Role of Parental Support - Steigmann, Felix (Frontiers in Education, 2020)
Inclusive education for persons with disabilities, although an internationally recognized human right, is far from being fully and adequately implemented. Since this crucial human right does not only apply to citizens, the lack of implementation holds true for refugees, too. Therefore, the present research elaborates on the extent to which the right to inclusive education is ensured for refugee children with disabilities in Berlin as well as on the obstacles and challenges with regard to access to this right. The theoretical basis of this research is formed by an outline and discussion of the manifold legal frameworks on different relevant levels of law and is contextualized by pertinent key concepts. Shedding light on the discrepancy between theory and practice, problem-centered expert interviews with six social workers in Berlin were conducted. These interviews were evaluated and analyzed according to the so-called Grounded Theory. It will be shown that apart from structural shortcomings and resource shortages, the parents’ capacity is one of the decisive aspects on which the prospects of inclusive schooling depend on. Within this context, the research focuses on the parent’s capacity in terms of, inter alia, knowledge about the education and support system and their personal conditions in either facilitating or constraining their children’s access to inclusive education as well as on the importance of social worker’s support and consultation measures which aim at strengthening the parent’s capacity. Interestingly, this approach shifts away the focus from accusations on a structural level of policymaking to suggestions of improving low-threshold support systems.